Hhex regulates murine lymphoid progenitor survival independently of Stat5 and Cdkn2a. Issue 7 (4th March 2020) - Jackson, Jacob T.; O'Donnell, Kristy; Light, Amanda; Goh, Wilford; Huntington, Nicholas D.; Tarlinton, David M.; McCormack, Matthew P.
Abstract: The transcription factor Hhex (hematopoietically expressed homeobox gene) is critical for development of multiple lymphoid lineages beyond the common lymphoid progenitor. In addition, Hhex regulates hematopoietic stem cell (HSC) self‐renewal, emergency hematopoiesis, and acute myeloid leukemia initiation and maintenance. Hhex mediates its effects on HSCs and acute myeloid leukemia stem cells via repression of the Cdkn2a tumor suppressor locus. However, we report here that loss of Cdkn2a does not rescue the failure of lymphoid development caused by loss of Hhex. As loss of Hhex causes apoptosis of lymphoid progenitors associated with impaired Bcl2 expression and defective Stat5b signaling, we tested the effects of rescuing these pathways using transgenic mice. Expression of the anti‐apoptotic factor Bcl2, but not activated Stat5, rescued the development of T‐, B‐, and NK‐cell lineages in the absence of Hhex. These results indicate that Bcl2 expression, but not Stat5b signaling or loss of Cdkn2a, can overcome the lymphoid deficiencies caused by the absence of Hhex, suggesting that the primary role of this transcription factor is to promote survival of lymphoid progenitors during early lymphoid development. Abstract : The homeobox transcription factor Hhex is essential for lymphopoiesis. Bcl2, but not activated Stat5b or the absence of Cdkn2a, rescues Hhex‐null lymphoid development. Thus, Hhex's role in lymphopoiesis differs from its role in HSC self‐renewal (which is rescued by loss of Cdkn2a), and Hhex promotes lymphoid survival independently of Stat5.